Digitisasi arsip dan doktrin religius pada komunitas Kristen Mormon - Harry Bawono (Perpustakaan Universitas Gadjah Mada, 2024)
Introduction. This research examines two questions: first, what is the relationship between archive digitalization and religious doctrines within the Mormon Christian Community? Second, how do these implications affect the interpretation of archival spirituality? The Mormon Christian Community has developed archival institutions as one of the early organizational units and established the world's largest digital genealogical archive site. This site is open and accessible to anyone. However, studies on the connection between archive digitalization and Mormon religious doctrines are still relatively scarce. Data Collection Methods. The research used a qualitative method based on archival research and was conducted in Indonesia from July to October 2022. Data Analysis. The researchers used technical data analysis techniques such as selection, reduction, categorization, and conceptualization. Results and Discussion. The familysearch.org site is a digital genealogical archive portal developed by the Mormon Christian Community. This portal evidences that archival spirituality within this community encompasses the comprehensive management of archives legitimized and oriented toward religious doctrines. Conclusion. Archive digitalization is a part of sacred practices. In this context, archival spirituality occurs as archive management receives legitimacy and orientation from religious doctrines. Therefore, religious communities can advance archive digitalization by employing religious doctrines as a basis.